Remote Working Environment Challenges in the Context of the Covid-19 Pandemic - Al- Rfou, Ahmad. N (Journal of Asian Business Strategy, 2021)
As a result of the COVID 19 pandemic, employees have begun working remotely from home, which has resulted in new challenges in the work environment. The purpose of this paper is to identify the challenges of the remote work environment in the context of the COVID-19 pandemic and to determine the level of these challenges according to the worker’s gender and job. This study was conducted on 11 Jordanian IT companies at the end of 2020. The intentional sample was used,125 valid questionnaires were used in the analysis. The results show that the respondents’ perceptions of the challenges of the remote work environment in the context of the COVID-19 pandemic were high. There are also statistically significant differences at the level of significance (α≤0.05) for the level of challenges in the remote working environment according to gender (male/female) in favor of females and according to job level (supervisory or non-supervisory) in favor of non-supervisory jobs. To increase organisational performance, all parties—employees, families, and management—must cooperate to overcome the challenges of the remote work environment.